Injury and Healing Response of Healthy Peripheral Arterial Tissue to Intravascular Lithotripsy: A Prospective Animal Study - Liu, Feng; Ge, Yangyang; Rong, Dan; Zhu, Yating; Yin, Jianhan; Sun, Guoyi; Jia, Xin; Guo, Wei (Frontiers in Cardiovascular Medicine, 2022)
Objectives Intravascular lithotripsy (IVL) is a novel clinical technique for the management of severely calcified lesions. However, the biological effects of shock wave on the healthy arterial tissue have not been demonstrated. The preclinical safety study aimed to investigate the vascular response to IVL shock wave compared to plain old balloon angioplasty (POBA) in porcine peripheral arteries. Methods The left and right iliofemoral arterial segments of 16 mini-pigs were subjected to IVL and POBA, respectively. The vascular response was evaluated using quantitative vascular angiography (QVA), light microscopy, and scanning electron microscopy (SEM) at 0, 5, and 28 days. Results With the emission of shock wave, adjacent muscle contraction was observed. QVA showed there was no statistically significant difference in percent diameter stenosis and late lumen loss between the two groups. SEM examination showed the endothelial cell layer was intact in both groups at all timepoints. Under light microscopy, no area stenosis was observed. However, IVL shock wave resulted in significantly higher percent area stenosis and intimal area at 28 days. Neointima score showed a trend toward a higher rate in the IVL group, although there was no statistically significant difference at 28 days. There were no statistically significant differences in the scored parameters between groups at all timepoints. However, the parameters of inflammation and neointima showed a trend toward higher scores in the IVL group. After disruption of the internal elastic lamina, the arteries demonstrated significantly neointimal thickening. Conclusions The safety and operability of IVL are comparable to POBA. The histological response of healthy arteries to IVL shock wave is mild and sustained. IVL shock wave do not cause serious vascular tissue damage, especially endothelial denudation.